Evaluation of blood alcohol levels in samples taken from medico-legal cases in Manaus, Northern Brazil - Andrade Canto, Paulo Abraão; Gama dos Santos Rodrigues, Adriane; Gomes Silva, Suniá; Guimarães Versiani, Fernanda; Lima Versiani, Francivaldo; dos Santos Magalhães, Igor Rafael (Revista Brasileira de Criminalística, 2023)
Historically, the alcohol consumption has been associated to occurrence of different crimes, including homicides, rapes and sexual assault, among others. Hence, the aim of this study was to evaluate the blood alcohol levels (BAC) in samples taken from medico- legal cases in Manaus, northern Brazil. An observational retrospective study covering May-2018 through April-2019 was carried out and the database of the referral center was employed. In total, 142 cases were evaluated. The mean age of participants was 36.2 ± 10.9 years (range 18-78 years, CI 95% 34.34-38.42) and the majority of them was male (87.32%), single (66.20%), attended the secondary school level (47.89%) and living in the city of Manaus at the time of the incidence (61.70%). The mean BAC was 0.20 ± 0.08 g/dL (range 0.1-0.64 g/dL, CI 95% 0.10-0.15). In relation to the incident, the weekday with most cases was Sunday (30.28%) and in the early morning (24 to 06 hours; 40.14%). Only a small percent was alive before the blood draw (7.04%) and traffic accidents were the most registered occurrence (61.27%). Cocaine was also found in some cases (4.23%). Highest BAC levels were observed for the homicide cases whereas lowest BAC values were attained for the suicide cases (p=0.01). Furthermore, there was a weak positive correlation between age and BAC (r=0.27; p=0.01). For the first time, the study of BAC in samples taken from medico-legal cases was performed in Manaus. Taking into account the results, authorities may develop dedicated strategies to deal with this problem.